2016
DOI: 10.1115/1.4032283
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Gain Scheduling Strategy for an Internal Model Control-Based Boost Pressure Controller in Variable Geometric Turbocharger System of Diesel Engines

Abstract: This paper proposes a model-based gain scheduling strategy of a Skogestad internal model control (SIMC)-based boost pressure controller for passenger car diesel engines. This gain scheduling strategy is proposed with a new scheduling variable to handle the nonlinear variable geometric turbocharger (VGT) plant characteristics. The scheduling variable is derived from the pressure ratio between the exhaust and intake manifolds and the exhaust air-to-fuel ratio to estimate the static gain of the VGT plant, which v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The inlet air mass flow ( MAF ) and the boost pressure ( P b ) are the most common feedback signals used for diesel engine air path control, significantly important for the aforementioned performance variables. 15 Due to problems such as sign change for DC gains and nonlinearity in input–output relations observed for an MAF P b controller, new architectures have been proposed for manipulation of the exhaust gas recirculation (EGR) and variable geometry turbine (VGT) control valves. 68 In the work by Park et al, 6 for example, it is shown that the cylinder oxygen ratio, χ cyl , has a close and monotonic correlation to diesel engine-out NO x emissions and is used as a feedback-estimated signal to be managed by controlling the EGR valve.…”
Section: Introductionmentioning
confidence: 99%
“…The inlet air mass flow ( MAF ) and the boost pressure ( P b ) are the most common feedback signals used for diesel engine air path control, significantly important for the aforementioned performance variables. 15 Due to problems such as sign change for DC gains and nonlinearity in input–output relations observed for an MAF P b controller, new architectures have been proposed for manipulation of the exhaust gas recirculation (EGR) and variable geometry turbine (VGT) control valves. 68 In the work by Park et al, 6 for example, it is shown that the cylinder oxygen ratio, χ cyl , has a close and monotonic correlation to diesel engine-out NO x emissions and is used as a feedback-estimated signal to be managed by controlling the EGR valve.…”
Section: Introductionmentioning
confidence: 99%